Organizational democracy, ethics and leadership: the mediating role of organizational politics - Clarke, Martin (Cranfield University, 2011)
There has been a growing concern amongst commentators about the disconnection between the apparent pluralisation of society and the relatively limited adoption of democratic practices in the corporate workplace. This paper examines the experience of employees in an international broking company in order to explore the extent to which a political leadership perspective can provide insight into furthering organizational democratisation. Attention is given to the integral relationship between democracy, ethics and a political mindset, and the influence this has upon others. In the account reported here, the ethical and developmental agenda of one influential senior manager is central to both the enactment of politics and the form of democratisation which it enables.